Survival and growth of microscopic fungi derived from tropical regions under future heat waves in the Pannonian Biogeographical Region - Tischner Zsófia Bernadett (FUNGAL BIOLOGY, 2022)
Warming and heat waves are predicted by different climate models in the near future in the Pannonian Biogeographical Region (PBR). These climatic effects may have impact on the prevalence and distribution of certain fungal species of this area. In this study the effects of predicted climate scenarios were tested on fungi being endemic or unintentionally introduced by global trade from regions of warm temperate climate. Common fungal species were selected for the study and exposed to heat waves during 7 days according to two climate scenarios: one moderately (RCP 4.5, Tavg = 27 °C, Tmax = 35 °C, RH: 100%) and one strongly pessimistic (RCP 8.5, Tavg = 30 °C, Tmax = 40 °C, RH: 100%) that include predictions for the Central Hungarian Region for July 2050. According to our results, Aspergillus flavus, Aspergillus niger, Aspergillus tubingensis and Fusarium strains introduced from tropical regions tolerated heat waves, unlike Penicillium and Talaromyces spp. and endemic Cladosporium spp. which were unable to grow under the RCP 8.5 treatment. The effects of climate change on fungi raise new issues not only from economic and health perspectives, but also in relation with plant protection and environment. Our results suggest that heat waves driven by climate change promote the colonization and growth of the tested strains of non-native fungi more likely than that of the native ones.